How the current fourth industrial revolution effecting the leadership? - Avny, Ronnen (Studia Mundi – Economica, 2021)
Innovation leadership is critical in enhancing a firm’s success in today’s changing markets. This research investigates the changes in entrepreneurial leadership attributes amid the fourth industrial revolution and the fast pace of technological advancement. This study helps to understand how leadership traits may help entrepreneurs fully exploit the advantages of this revolution and gain a competitive advantage. The content analysis method used for this research utilized written data regarding 23 leaders from 20 companies from the latest 19th century during the first industrial revolution until the current fourth industrial revolution. Results reveal noticeable leadership attributes emphasized in the fourth industrial revolution, such as communication, coaching, innovation, forecasting future, team-builder, and more. Those attributes are in tight correlation with the current novel digital leadership paradigm and the known effects of the fourth industrial revolution on the firms and leaders. Results reveal that current entrepreneurs tend to be open-minded while avoiding rejecting innovation from other firms and are willing to share the experience with the adjacent technology ecosystem.